Secretory Expression of an Alkaline Alginate Lyase With Heat Recovery Property in Yarrowia lipolytica - Liu, Lu; Wang, Zhipeng; Zheng, Zhihong; Li, Ze; Ji, Xiaofeng; Cong, Haihua; Wang, Haiying (Frontiers in Microbiology, 2021)
Alginate lyase possesses wide application prospects for the degradation of brown algae and preparation of alginate oligosaccharides. Despite many enzymes of this type have been reported, the alginate lyases with unique properties are still relatively rare. In present work, an alginate lyase abbreviated as Alyw203, was cloned from Vibrio sp. W2 as well as expressed in the Yarrowia lipolytica of food-grade. The peak activity of the current enzyme appears at 45 °C with the molecular weight of approximately 57.0 kDa. Interestingly, Alyw203 exhibits unique heat recovery performance, returning above 90% of its initial activity in the following of incubation for 20 min at 10 °C. Meanwhile, the highest activity is obtained under alkaline conditions of pH 10.0. Additional, Alyw203 is a NaCl-independent and metal ions-resisted alginate lyase, which is conducive to high activity in various ionic environments. Enzymatic degradation products are concentrated in the oligosaccharides of DP1-DP2. Alyw203 is a potential choice for industrial production owing to its alkali applicability, heat recovery performance and high oligosaccharide yield.